Implementasi Standar Pelayanan Kefarmasian di Apotek Kupang - Maria Meliana Waty Parera; Susi Ari Kristina; Nanang Munif Yasin (Faculty of Pharmacy, Universitas Gadjah Mada)
According to applicable standards, pharmaceutical services strongly support the role of pharmacists in realizing quality pharmaceutical services to protect patients and the community and provide legal certainty for pharmaceutical personnel. This study aims to evaluate the implementation of pharmaceutical service standards in pharmacies by pharmacists in Kupang City. This study uses a quantitative descriptive approach. Data were collected using a questionnaire adapted from Regulation of the Minister of Health Number 73 of 2016 concerning Pharmaceutical Service Standards in Pharmacies. The population in this study were all pharmacies in Kupang City, totaling 90 pharmacies based on data from the Health Service, with valid pharmacy permits. Respondents are pharmacists who have a valid practice license in pharmacies and are willing to participate in the survey. A total of 66 respondents returned the questionnaire, and 64 were declared complete and qualified for analysis. Data were analyzed using univariate analysis with SSPS 25. The results showed that 53.75% of pharmacies in Kupang City had implemented pharmaceutical service standards in pharmacies by Regulation of the Minister of Health Number 73 of 2016, while 46.25% have not implemented service standards properly. Pharmacies that manage pharmaceutical preparations, medical equipment, and disposable medical equipment (BMHP) according to standards are 66.1%, and clinical pharmacy services are 41.4%. The conclusion shows that pharmaceutical service standards in pharmacies have not been carried out optimally by pharmacists in Kupang City.